National Teleconsultation Service in India: eSanjeevani OPD - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
India's achievements in the field of health leave much to be desired. Infant and child mortality and morbidity and maternal mortality and morbidity affect millions of children and women. The burden of disease continues to be high in the country with life expectancy at around 69 years, MMR at 113 per 100,000 live births and IMR at 32 per 1,000 live births still remain high. The public healthcare system in rural areas in India is not only underutilized due to poor quality of healthcare services, but is also inadequate in terms of population coverage. Further, gross shortage of specialist and chronic absenteeism of healthcare staff makes the situation even worse. Majority of the specialists/doctors live in urban areas and in such a situation telemedicine offers an ideal solution. The utmost need of telemedicine was felt when OPD services came to a halt due to nationwide COVID-19 lockdown. To deal with the situation, on April 13, 2020, the Ministry of Health & Family welfare launched National Teleconsultation service via an online portal "eSanjeevani OPD - Stay Home OPD". This paper provides a detailed account of National Teleconsultation portal, eSanjeevani OPD. The paper discusses the current status of eSanjeevani OPD, its salient features, challenges in the way of successful adoption of eSanjeevani OPD and comparison of eSanjeevani OPD with global telemedicine platforms. Further, this paper also proposes a pilot study to explore the factors that act as barriers and facilitators for the utilization of eSanjeevani OPD.
Keywords: 330; eSanjeevani OPD; Teleconsultation; Telemedicine; India